2001
DOI: 10.1029/2000gl012044
|View full text |Cite
|
Sign up to set email alerts
|

Parameterizing tidal dissipation over rough topography

Abstract: Abstract.The traditional model of tidal dissipation is based on a frictional bottom boundary layer, in which the work done by bottom drag is proportional to a drag coefficient and the velocity cubed. However, away from shallow, coastal regions the tidal velocities are small, and the work done by the bottom boundary layer can account for only weak levels of dissipation. In the deep ocean, the energy flux carried by internal waves generated over rough topography dominates the energy transfer away from barotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
441
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(463 citation statements)
references
References 18 publications
19
441
2
1
Order By: Relevance
“…1a). Despite the differences in the tide model used, the distribution of Ec in the present study is basically the same as that obtained in previous studies 32 .…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…1a). Despite the differences in the tide model used, the distribution of Ec in the present study is basically the same as that obtained in previous studies 32 .…”
Section: Methodssupporting
confidence: 77%
“…In previous studies 7,8,11 , Ec was empirically derived from the parameterized wave drag term in their barotropic tide model 32 (that is, vertically integrated model). Conversely, in this study, we use Ec explicitly calculated from a threedimensional tide model 14 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Egbert and Ray [44] estimated that the M 2 tide dissipation is 40 GW, which is the same order as 10 GW from the results of Tian et al [43]. Simmons et al [45] incorporated the tidal mixing parameterization [46] into MOM3. Their results showed that the scheme resulted in a substantial reduction of temperature/salinity biases.…”
Section: The Effects Of Vertical Mixing On Mocmentioning
confidence: 73%
“…Typical values for the deep ocean (N $ 10 À5 s À1 , U $ 1 cm/s) thus give k ' 2p/ (10 km). This is the same order as the optimal value of k employed in a recent deep ocean internal wave parameterization scheme [Jayne and St. Laurent, 2001], in which k was set to minimize the difference between modelled and observed tides. In rough regions of the ocean we assume the wave amplitude is limited by nonlinear effects in which case we take h ' C a U/N, with C a = 0.5.…”
Section: Discussionmentioning
confidence: 99%